2013
DOI: 10.2134/agronj2012.0069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arbuscular Mycorrhizal Fungi on Seed and Protein Yield under Water‐Deficit Stress in Mung Bean

Abstract: Arbuscular mycorrhizal fungi are considered to have the potential to increase the tolerance of host plants to water-defi cit stress. Th is is due to their apparent role in water and nutrient uptake and transfer to their host plants. To evaluate the eff ects of mycorrhizal fungi species and water-defi cit stress on mung bean [Vigna radiata (L.) R. Wilczek var. radiata] plants, a 2-yr split-plot experiment based on a randomized complete block design with three replications was conducted in the fi eld in 2009 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 43 publications
4
19
0
1
Order By: Relevance
“…Under soil water deficit AM symbiosis generally confers better growth performance, greater photosynthetic efficiency, and higher antioxidant system defense systems of host plants, including bean, wheat, and rice plants (Habibzadeh et al, 2013;Moucheshi et al, 2012;RuizSánchez et al, 2010). Our study also indicated that the AMF inoculations presented higher activities of tissue SOD, POD, and CAT during SWD, in company with lower levels of H 2 O 2 and O 2…”
Section: Discussionmentioning
confidence: 99%
“…Under soil water deficit AM symbiosis generally confers better growth performance, greater photosynthetic efficiency, and higher antioxidant system defense systems of host plants, including bean, wheat, and rice plants (Habibzadeh et al, 2013;Moucheshi et al, 2012;RuizSánchez et al, 2010). Our study also indicated that the AMF inoculations presented higher activities of tissue SOD, POD, and CAT during SWD, in company with lower levels of H 2 O 2 and O 2…”
Section: Discussionmentioning
confidence: 99%
“…This result accorded with the finding of Zhao et al (2015). The positive effect of AMF on growth performance of the host plant is likely due to the improvement in P nutrition and water by extraradical hyphae (Habibzadeh et al, 2013;Wu et al, 2013). In addition, P. occultum-inoculation performed relatively greater effects on stimulating biomass production than F. mosseae-inoculation, especially under WW, which is associated with the compatibility between AMF and host plants.…”
Section: Biomass Productionmentioning
confidence: 98%
“…Compared to non-mycorrhizae plants, the bigger antioxidant enzyme activity in plants inoculated with AMF was related with the lower lipid peroxidation accumulation, which indicates lower oxidative harm in the mycorrhized plants. In a similar manner, Habibzadeh et al [119] reported that enhancement in tolerance to saline stress ("Behta" and "Piazar") of the tomato inoculated with R. intraradices was associated with a higher P, K, and Ca intake and with lower Na toxicity. The net photosynthesis enhanced mycorrhization through increasing stomatal conductance and protecting PSII [120].…”
Section: Inducing Salinity Stress Tolerance Through Inoculation Of Mymentioning
confidence: 72%